PENGARUH EKSTRAK ETANOL DAUN TAPAK DARA (Catharanthus roseus (L.) G. Don.) VARIETAS ALBUS TERHADAP PERTUMBUHAN TANAMAN KEDELAI (Glycine max (L.) Merr.) cv. ANJASMORO - Suyadi, Muhammad (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2026)
Soybean is an important commodity in Indonesia because it is a source of protein in addition to being a source of fat, vitamins, and minerals for the community. The need for soybeans increases every year along with the increasing population growth. So it is necessary to do plant breeding to improve the superior nature of soybeans. One of them is with antimitotic compounds found in periwinkle (Catharanthus roseus (L.) G. Don), namely vincristine and vinblastine. This study aims to determine the effect of variations in the length of immersion in 70% ethanol extract of periwinkle leaves on the growth of soybean plants (Glycine max (L.) Merr.) cv. Anjasmoro. This study uses an experimental method with a Linear Regression test consisting of one factor, namely soaking time (8, 16, and 24 hours). The results of statistical data processing showed a positive effect on the growth of soybean plants. The results obtained in the study were the treatment of immersion 70% ethanol extract of periwinkle leaves at a concentration of 0.4 ppm with a soaking time of 24 hours gave the results of plants with habitus characteristics that were superior to others. This is evidenced by the plant habitus characters, namely plant height, number of petioles, number of flowers, and number of root nodules that are superior to other immersion treatments and controls. While microscope observations on epidermal cells have a longer size than other treatments and controls.